Implementasi Teori dan Penemuan Hukum dalam Rekomendasi Ombudsman RI : Kaitan Norma Hukum dan Keadilan Administratif - Khofifah Pane; Irwan Triadi (Catalist Indo Publisher, 2025)
Recommendations issued by the Ombudsman of the Republic of Indonesia are a crucial instrument for upholding administrative justice and preventing maladministration in public service delivery. This study aims to analyze the Ombudsman’s authority in issuing recommendations and examine its relationship to legal discovery theory, as well as its reflection of justice values in government administration. Using a normative juridical method through a literature-based review of legal scholarship, legislation, and relevant Ombudsman recommendations, the study finds that these recommendations function not merely as administrative decisions but also as a manifestation of the legal discovery process. In interpreting norms and determining appropriate remedies for public reports, the Ombudsman applies principles of legality and good governance while balancing legal certainty, utility, and justice. The study concludes that the Ombudsman’s recommendation authority plays a substantive role in strengthening accountability in public administration and ensuring that government actions remain aligned with citizens’ rights and the broader principles of administrative justice.